HUBUNGAN KUALITAS TIDUR DENGAN KELELAHAN SUBJEKTIF PADA PEGAWAI DINAS KESEHATAN PROVINSI NUSA TENGGARA BARAT DI MASA PANDEMI COVID-19 - I Gusti Bagus Ngurah Ananda Rai Prema Wianta; Ni Ketut Sutiari (ARCHIVE OF COMMUNITY HEALTH, 2022)
Handling Covid-19 pandemic in various region, can lead to work fatigue. Work fatigue can be influenced by various factors, such as sleep quality that related to circandian rhythm. This study aims to determine the proportion of work fatigue, and the correlation between sleep quality factors and work fatigue in Public Health Service Employees of NTB Province during the Covid-19 pandemic. This study is a quantitative study with cross-sectional design, using the Industrial Fatigue Research Committee (IFRC) and Pittsburgh Sleep Quality Index (PSQI) questionnaires for collecting the data. Population of this study is 110 Public Health Service Employees of NTB Province. The analysis was performed with univariable and bivariable (chi-square test). The results of the univariable analysis, showed more than half of the respondents experienced fatigue (52.73%), and most of the respondents had poor sleep quality (69.09%). Meanwhile based on the bivariable analysis, there was a significant correlation between sleep quality and work fatigue (p=0.000). Suggestions are to be able to recognize the symptoms of fatigue in general; stretching before, in between and after work; and do physical activity for at least 30 minutes a day to improve sleep quality of Public Health Service Employees of NTB Province. Keyword : Subjective Fatigue, Sleep Quality, IFRC, PSQI